The idea of Europe : from antiquity to the European Union - Pagden, Anthony (2002)
Introduction / Anthony Pagden – Europe : conceptualizing a continent / Anthony Pagden – Some Europes in their history / J.G.A. Pocock – "Europe" in the Middle Ages / William Chester Jordan – The republican mirror : the Dutch idea of Europe / Hans W. Blom – The Napoleonic empire and the Europe of nations / Biancamaria Fontana – Homo politicus and homo oeconomicus : the European citizen according to Max Weber / Wilfried Nippel – The European self : rethinking an attitude / Michael Herzfeld – European nationalism and European union / Ariane Chebel d'Appollonia – From the ironies of identity to the identities of irony / Luisa Passerini – Muslims and European identity : can Europe represent Islam? / Talal Asad – The long road to unity : the contribution of law to the process of European integration since 1945 / Philip Ruttley – The euro, economic federalism, and the question of national sovereignty / Elie Cohen – Identity politics and European integration : the case of Germany / Thomas Risse and Daniela Engelmann-Martin – Nationalisms in Spain : the organization of convivencia / Andrés de Blas Guerrero – The Kantian idea of Europe : critical and cosmopolitan perspectives / James Tully